Somatotype in 11 years old Macedonian adolescents - Bojadzieva Stojanoska, Biljana; Matveeva, Niki; Zafirova, Biljana; Trpkovska B; Kavecan, Ivana (Macedonian Association of Anatomists and Morphologists, 2018)
Objectives. The aim of this study was to evaluate sex and ethnic differences of somatotype in Macedonian adolescents at the age of 11 years. Subjects and Methods. In this study 315 adolescent students (167 males and 148 females), from Macedonian and Albanian nationality at age of 11 years were included from primary schools in two cities: Skopje and Strumica in R. Macedonia. Ten anthropometric parameters were measured using standard equipment and measurement technique to assess the somatotype according to Heat–Carter somatotyping method. Results. Although there were not significant sex and ethnic differences of somatotype components between the groups at the age of 11 years, from the obtained results we concluded that males and females of Macedonian ethnic group had higher values for endomorph component than their Albanian pears, who had higher values for mesomorph and ectomoph component. Conclusion. Ethnic group should be taken in mind for easier evaluation and understanding of differences in anthropometric parameters of growth and body composition in Macedonian adolescents.
Keywords: somatotype; Macedonians; adolescents